Microbial Communities of the Drinking Water With Gradient Radon Concentration Are Primarily Contributed by Radon and Heavy Metal Content - Nayak, Tilak; De, Debjit; Karmakar, Parimal; Deb, Argha; Dhal, Paltu Kumar (Frontiers in Environmental Science, 2021)
Radon and heavy metal (HM) contamination in drinking water and their impact on health have been reported earlier. However, relatively little is known about the microbial community in drinking water with gradients of radon and the drivers of microbial community patterns in such water. With this view, we first examine microbial dynamics of drinking water in the permissible level of 93 ± 2 Bq/l as control, 510 ± 1.5 6 Bq/l and 576 ± 2 Bq/l as medium, and 728 ± 3 Bq/l as high radon-containing tube wells from Dumka and Godda districts, which comes under a major fault of the eastern fringes of India. Attempts have also been made to predict the impact of the radon contamination gradient and other water environmental parameters on community structure. The measured physicochemical character revealed strong clustering by the sampling site with respect to its radon and HM content. The radon-contaminated sites represent HM-rich nutrient-limited sites compared to the control. Radon (Rn), HM (Pb, Cu, and As), and total suspended solids (TSSs) were the most determinant variable among the parameters and influenced the microbial community composition of that region. The microbial diversity of those sites was lower, and this measured diversity decreased gradually on the sites with an increased gradient of radon contamination. The dominant microbial families in the contaminated sites were Moraxellaceae, Chitinophagaceae, unclassified Candidatus Azambacteria, unclassified Candidatus Moranbacteria, unclassified Candidatus Collierbacteria, and Gammaproteobacterial members, which are reported to abundantly inhabit radiation and chemolithotrophic environments and pose better radionuclide protective mechanisms, while the bacterial members dominant in the control site were Comamonadaceae, Rhodocyclaceae, Nitrospirales Incertae Sedis, cvE6, unclassified Woesearchaeota (DHVEG-6), and Holophagaceae, which are reported to be abundant in natural soil and drinking water, and labile in harsh environments. Relative sequence abundance of Comamonadaceae was decreasing on the sites with an increasing radon gradient, while the opposite trend was observed for Chitinophagaceae. The distribution of such microbial assemblages is linked to radon and heavy metal, highlighting that taxa with distinct environmental preferences underlie apparent clustering by sites; thus, we can utilize them for biostimulation-based in situ bioremediation purposes.